Perception of smoking habits and related diseases among society - Gupta, Utkarsh; Agarwal, Rajat; Agarwal, Rajesh; Kumar, Amit; Sharma, Divyendu (International Journal Of Community Medicine And Public Health, 2020)
Background: Smoking is practiced by a third of world’s population. Tobacco is leading cause of deaths world over. Six million people (1/8 second) die from tobacco each year. Objective of this study was to study demographic profile and awareness regarding tobacco smoking among people of Rohilkhand, Bareilly. Methods: Randomly selected individuals of Rohilkhand region. Questionnaire method involved. Results: Among 1040 sample size, 70% were males with mean age of 37.68 years. 73.94% population belonged to upper lower socio-economic class. 52% (62.9% male and 26.6% females) were current smokers of which 60.6% were exclusive beedi smokers. 50% were unaware of oral and lung cancer due to smoking. 34% were unaware about effects of passive smoking. 48.48% smokers report cough with expectoration as commonest symptom. 60% finds peer group influential for the behavior. 76.9% smokers are willing to quit smoking. 63.4% are open for counseling. 26% were unaware of ban/law related to smoking in public places. 68% believe there is increasing trend in prevalence of its use, among minors, educational institutes and hospitals. Conclusions: Despite high awareness of ill effects of smoking, there is an increasing trend in prevalence of smoking with an increased involvement of minors attributed to peer pressure. People are unaware of passive smoking and its harmful effect on body. Moreover, advertisements, visuals and captions have failed in making an impact. There occurs a need of awareness programmes, intervention sessions, medical therapy and strict anti-smoking laws by the government, social welfare and healthcare volunteers to help people quit and control the menace in society.